Atividade larvicida de fungos da Amazônia Brasileira para o controle de mosquitos vetores de doença - Bücker, Augusto (2008)
Extracts from five genera of endophytic fungi and a species of basidiomycete fungus were used to evaluate larvicidal activity against third stage larvae of Aedes aegypti and Anopheles nuneztovari. The biological material, belonging to the Pycnoporus genus, was collected in the Adolpho Ducke Reserve of the National Institute of Amazonian Research - INPA, located on the outskirts of Manaus - AM. The other species of endophytic fungi were obtained in collaboration with the Laboratory of Bioactive Products of Microbial Origin, at the Federal University of Amazonas - UFAM. Endophytic fungi come from plants at Fazenda da Agronomia - UFAM, BR Manaus - Rio Branco. Extracts of the mycelium and the metabolic medium of the endophytic fungi, of the genera: Pestalotiopsis, Penicillium, Trichoderma, Xylaria and an unknown (FED-15) were used. The biological tests started with the selective bioassays, carried out on larvae of the 3rd stage of A. aegypti. The extracts of the basidiomycete fungus Pycnoporus sanguineus and the endophytic fungus Pestalotiopsis virgulata showed the best larvicidal yields. In the second stage, the dose bioassays were performed only with the fungi P. sanguineus and P. virgulata. To obtain the crude extracts on a preparative scale, the fungi were grown in a liquid culture medium - MID, thereby obtaining two types of extracts: mycelial aceto-ethanolic extract and the aceto-ethanolic extract of the metabolic medium. Four (04) of the nine (09) fungi extracts studied showed toxicity against A. aegypti larvae for LC50 <500 µg / ml. And three (03) of the seven (07) extracts of fungi studied showed toxicity against A. nuneztovari larvae for LC50 <500 µg / ml. These results suggest that in both mycelial extracts of the fungi P. sanguineus and P. virgulata tested, there is the presence of bioactive substances capable of causing mortality in the larvae of mosquitoes of the genera Aedes and Anopheles.